Applying family‐based treatment (FBT) to three clinical presentations of avoidant/restrictive food intake disorder: Similarities and differences from FBT for anorexia nervosa. Issue 4 (22nd December 2018) - Lock, James; Robinson, Athena; Sadeh‐Sharvit, Shiri; Rosania, Kimberly; Osipov, Lilya; Kirz, Nina; Derenne, Jennifer; Utzinger, Linsey
Abstract: Objective: This article uses three brief case reports to illustrate how family‐based treatment (FBT) can be used to treat pre‐adolescents with avoidant/restrictive food intake disorder (ARFID). Method: We present case material illustrating how FBT can be used in three different clinical presentations of ARFID: (1) low appetite and lack of interest; (2) sensory sensitive eaters; and (3) fear of aversive consequences eaters—all without shape or weight concerns. Results: This case material illustrates that the main principles of FBT—agnosticism as to the cause of the illness, externalization, emphasizing the seriousness of ARFID, parental empowerment, behavioral consultation, and practical behavioral focus—are applicable for a range of ARFID clinical presentations. Common challenges in this patient group include (1) promoting urgency; (2) challenging long term behavioral accommodation; (3) lack of parental alignment, parental fatigue, (4) and co‐morbid psychiatric problems in the patients. Strategies to address these problems are described. Conclusion: FBT can be adapted for children with ARFID using the main principles of the approach.